Tripolyphosphate-Crosslinked Chitosan/Gelatin Biocomposite Ink for 3D Printing of Uniaxial Scaffolds - Fischetti, Tiziana; Celikkin, Nehar; Contessi Negrini, Nicola; Farè, Silvia; Swieszkowski, Wojciech (Frontiers in Bioengineering and Biotechnology, 2020)
Chitosan is a natural polymer widely investigated and used due to its antibacterial activity, mucoadhesive, analgesic, and hemostatic properties. Its biocompatibility makes chitosan a favorable candidate for different applications in tissue engineering (TE), such as skin, bone, and cartilage tissue regeneration. Despite promising results obtained with chitosan 3D scaffolds, significant challenges persist in fabricating hydrogel structures with ordered architectures and biological properties to mimic native tissues. In this work, chitosan has been investigated aiming at designing and fabricating uniaxial scaffolds which can be proposed for the regeneration of anisotropic tissues (i.e., skin, skeletal muscle, myocardium) by 3D printing technology. Chitosan was blended with gelatin to form a polyelectrolyte complex in two different ratios, to improve printability and shape retention. After the optimization of the printing process parameters, different crosslinking conditions were investigated, and the 3D printed samples were characterized. Tripolyphosphate (TPP) was used as crosslinker for chitosan-based scaffolds. For the optimization of the printing temperature, the sol-gel temperature of the chitosan-gelatin blend was determined by rheological measurements and extrusion temperature was set to 20°C (i.e., below sol-gel temperature). The shape fidelity and surface morphology of the 3D printed scaffolds after crosslinking was dependent on crosslinking conditions. Interestingly, mechanical properties of the scaffolds were also significantly affected by the crosslinking conditions, nonetheless the stability of the scaffolds was strongly determined by the content of gelatin in the blend. Lastly, in vitro cytocompatibility test was performed to evaluate the interactions between L929 cells and the 3D printed samples. 2% w/v chitosan and 4% w/v gelatin hydrogel scaffolds crosslinked with 10% TPP, 30 min at 4°C following 30 min at 37°C have shown cytocompatible and stable characteristics, compared to all other tested conditions, showing suitable properties for the regeneration of anisotropic tissues.